Lecturers Perceptions of Changes in Muslim Students Behavior After the Use of Artificial Intelligence in Learning - Firdausi, Ahmad Robith (Al-Fikru: Jurnal Ilmiah, 2025)
This study was motivated by the rapid development of artificial intelligence that has transformed the learning process in higher education. The purpose of this study was to examine lecturers' perceptions of the impact of AI use, particularly on student behavior. Based on a qualitative approach through observation, in-depth interviews, and document analysis, the results of this study found that artificial intelligence has an ambivalent influence. On the one hand, artificial intelligence encourages students to be more independent in accessing information and completing tasks. However, on the other hand, this independence is not always followed by active participation in class discussions, which reduces academic interaction. In addition, concerns have arisen regarding academic ethics, such as plagiarism and low originality of work, as well as excessive dependence on technology that hinders critical thinking skills. In response to this, lecturers feel the need to adjust their roles and teaching strategies to be relevant to the digital era. These findings emphasize the importance of digital literacy and artificial intelligence ethics in higher education, in line with Selwyn and Norman's views on digital learning and technology ethics. Literacy and ethics enable students to use technology wisely.